Electrifying Hilly Remote Habitation by Solar Photovoltaic System - Madeti, S (Springer Science and Business Media Deutschland GmbH, 2022)
Considering escalating prices, global warming and difficulty in fuel transportation due to the remoteness of the site associated with conventional sources of energy, the use of locally available renewable sources of energy could be the best way to energize the un-electrified villages/hamlets in a clean and sustainable manner. India is endowed with a wealth of rich natural resources of energy such as solar, wind, biomass, small hydro, geothermal, tidal etc. Among different renewable resources of energy, solar energy is the best option for electrifying remote locations in India, as in most of the parts enough solar energy potential is available. In this paper, a solution for electrifying a remote hilly habitation using a solar photovoltaic system has been given and a reliable power design with 2 days battery backup has been proposed for the same. Further, the economic viability of the proposed system has also been carried out. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.